Synergistic effect of phosphodiesterase 4 inhibitor and serum on migration of endotoxin-stimulated macrophages. Issue 8 (November 2018) - Yang, Jing-Xing; Hsiung, Te-Chih; Weng, Fu-Chun; Ding, Shiau-Li; Wu, Chin-Pyng; Conti, Marco; Chuang, Tsung-Hsien; Catherine Jin, S-L
Macrophage migration is an essential step in host defense against infection and wound healing. Elevation of cAMP by inhibiting phosphodiesterase 4 (PDE4), enzymes that specifically degrade cAMP, is known to suppress various inflammatory responses in activated macrophages, but the role of PDE4 in macrophage migration is poorly understood. Here we show that the migration of Raw 264.7 macrophages stimulated with LPS was markedly and dose-dependently induced by the PDE4 inhibitor rolipram as assessed by scratch wound healing assay. Additionally, this response required the involvement of serum in the culture medium as serum starvation abrogated the effect. Further analysis revealed that rolipram and serum exhibited synergistic effect on the migration, and the influence of serum was independent of PDE4 mRNA expression in LPS-stimulated macrophages. Moreover, the enhanced migration by rolipram was mediated by activating cAMP/exchange proteins directly activated by cAMP (Epac) signaling, presumably via interaction with LPS/TLR4 signaling with the participation of unknown serum components. These results suggest that PDE4 inhibitors, together with serum components, may serve as positive regulators of macrophage recruitment for more efficient pathogen clearance and wound repair.